P. Ricoeur’s Creative Imagination: The Source of Narrative Identity and Social Justice - Aleksandravičius, Povilas (Problemos, 2023)
The paper analyses Paul Ricoeur’s concept of creative imagination and shows how this essential element of human consciousness determines personal and societal identity and how it can be a source of just social norms and of ‘good life’ (vie bonne). The imagination, which is characterized by semantic innovations and a heuristic function, creates a dynamic narrative defining a human being and opens as specific rationality surpassing purely argumentative rationality and allowing to solve conflicts of social norms. The ethical aspect of this process, implying a triple structure I/other/just institutiones, creates conditions for the realization of the dialectic of justice and love in the political space; due to the dialectic, innovative ways for the realization of social justice become possible. Critical questions intended to open up the perspective for further thinking are posed at the end of the paper.
Keywords: Ricoeur; creative imagination; narrative identity; social justice; love